Negative Modulation of trpm8 Channel Function by Protein Kinase C in Trigeminal Cold Thermoreceptor Neurons - Madrid-Montecinos, R; Rivera-Bravo, B; Pertusa-Pastor, M (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
TRPM8 is the main molecular entity responsible for cold sensing. This polymodal ion channel is activated by cold, cooling compounds such as menthol, voltage, and rises in osmolality. In corneal cold thermoreceptor neurons (CTNs), TRPM8 expression determines not only their sensitivity to cold, but also their role as neural detectors of ocular surface wetness. Several reports suggest that Protein Kinase C (PKC) activation impacts on TRPM8 function; however, the molecular bases of this functional modulation are still poorly understood. We explored PKC-dependent regulation of TRPM8 using Phorbol 12-Myristate 13-Acetate to activate this kinase. Consistently, recombinant TRPM8 channels, cultured trigeminal neurons, and free nerve endings of corneal CTNs revealed a robust reduction of TRPM8-dependent responses under PKC activation. In corneal CTNs, PKC activation decreased ongoing activity, a key parameter in the role of TRPM8-expressing neurons as humidity detectors, and also the maximal cold-evoked response, which were validated by mathematical modeling. Biophysical analysis indicated that PKC-dependent downregulation of TRPM8 is mainly due to a decreased maximal conductance value, and complementary noise analysis revealed a reduced number of functional channels at the cell surface, providing important clues to understanding the molecular mechanisms of how PKC activity modulates TRPM8 channels in CTNs. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.